2021
DOI: 10.1155/2021/9945187
|View full text |Cite
|
Sign up to set email alerts
|

New Visual Expression of Anime Film Based on Artificial Intelligence and Machine Learning Technology

Abstract: With the improvement of material living standards, spiritual entertainment has become more and more important. As a more popular spiritual entertainment project, film and television entertainment is gradually receiving attention from people. However, in recent years, the film industry has developed rapidly, and the output of animation movies has also increased year by year. How to quickly and accurately find the user’s favorite movies in the huge amount of animation movie data has become an urgent problem. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Ren et al [13]. used machine learning and computer vision to analyse large amounts of animated movie data.…”
Section: Literature Surveymentioning
confidence: 99%
“…Ren et al [13]. used machine learning and computer vision to analyse large amounts of animated movie data.…”
Section: Literature Surveymentioning
confidence: 99%
“…To strengthen the human-computer interaction function of VR animation and achieve better recognition performance, depth images, and color images should be combined to preprocess information data [14]. Wan, Y. et al pointed out that the number of animated movies is also increasing while the informationization of the film industry is developing, and proposed to innovate the visual presentation of animated movies by using computer vision and machine learning technology and put forward specific ideas [15]. Kumarapu, L. et al found that single-person pose estimation has been well developed, but multi-person pose estimation still has some technical problems.…”
Section: Introductionmentioning
confidence: 99%
“…The ML methods are applied in two main categories: (1) supervised method by predicting some output variable associated with each input sample and (2) unsupervised method that does not need any sample data and provides a prediction by considering input feature dataset. The ML methods are widely deployed in many applications based on different sensors and datasets such as quasidistributed smart textile [37], simultaneous assessment of magnetic field intensity [38], paddy rice seed classification [39,40], anime film visualization [41], eggplant seed classification [42], regional digital construction [43], flood mapping [44], and flood prevention [45]. Although the ML methods have provided promising results in many abovementioned applications, they suffer from lower coverage and generalization [1].…”
Section: Introductionmentioning
confidence: 99%